What happens when you tell someone you self-injure? The effects of disclosing NSSI to adults and peers - Hasking, P.; Rees, Clare; Martin, G.; Quigley, J. (BioMed Central Ltd., 2015)
Background: Non-suicidal self-injury (NSSI) is associated with significant adverse consequences, including increased risk of suicide, and is a growing public health concern. Consequently, facilitating help-seeking in youth who self-injure is an important goal. Although young people who disclose their NSSI typically confide in peers and family, it is unclear how this disclosure and related variables (e.g. support from family and friends, coping behaviours, reasons for living) affect help-seeking over time. The aim of this study was to advance understanding of the impact of disclosure of NSSI by young people and to investigate these effects over time. Methods: A sample of 2637 adolescents completed self-report questionnaires at three time points, one year apart. Results: Of the sample, 526 reported a history of NSSI and 308 of those who self-injured had disclosed their behaviour to someone else, most commonly friends and parents. Conclusions: Overall, we observed that disclosure of NSSI to parents facilitates informal help-seeking, improves coping and reduces suicidality, but that disclosure to peers might reduce perceived social support and encourage NSSI in others. We discuss these findings in light of their clinical and research implications.